Analysis, Modelling, Optimization, and Numerical Techniques ICAMI, San Andres Island, Colombia, November 2013 - Tost, Gerard Olivar; Vasilieva, Olga (Springer Proceedings in Mathematics & Statistics, 2015)
This book highlights recent compelling research results and trends in various aspects of contemporary mathematics, emphasizing applications to real-world situations. The chapters present exciting new findings and developments in situations where mathematical rigor is combined with common sense. A multi-disciplinary approach, both within each chapter and in the volume as a whole, leads to practical insights that may result in a more synthetic understanding of specific global issues-as well as their possible solutions. The volume will be of interest not only to experts in mathematics, but also to graduate students, scientists, and practitioners from other fields including physics, biology, geology, management, and medicine.